Recent developments on non-conventional fish culture media in Nigeria (2007)
Isolated successes have been recorded in fish farming in some African countries with observable potentials in Nigerian marine waters. In Nigeria, aquaculture is a recent development and it has been practiced in conventional cultural media which are land borne while non-conventional ones are mainly using the conventional culutre media. The fish farms constructed in the 1950's were constructed in isolated and far away from home locations hence, theft was rampant in these poverty stricken localities. Cultural land acquisition practices entrenched in the society also makes it difficult for non- indigenes, the youths and the poor who are interested in fish farming to acquire land for their fish culture projects. The acquisition of technical know- how requires the full and consistent support of government and financial institutions for bridging the deficiency between the supply and the demand of fish in the country. Both convectional and non-conventional culture media struggle with such constraints as in availiability of good feeds. Inadequate quantity and quality supply of fingerlings to stock the media and largely the under utilization of availabe water resources in Nigeria. Several countries in Asia and other parts of Africa have succeeded in improving the fish production and protein intake of their populations through the utilization of cheaper non-conventional culture media like the homestead pond, pens and cages. Nigeria can also do the same if the challenges and constraints highlighted are tackled.